Subalternidade de gênero: refletindo sobre a vulnerabilidade para violência domêstica contra mulheres no contexto da pandemia - Ramos, Bianca Gomes (Universidade Federal do Tocantins, 2023)
The present work starts from the understanding that violence against women does not appear with the pandemic of COVID-19. As oriented by the World Health Organization, the causes of violence against women have historical roots, that is, it is linked to historical and social factors, such as gender inequality, economic, structural machismo, among others. Therefore, this paper is justified by the need to expand studies that seek to discuss the increase of violence due to isolation, because there was a significant increase in family interaction, which associated with the symptoms of stress caused by the pandemic condition has potentiated an old health and social problem: violence against women. It is on this fact that this research proposes to focus. How has the pandemic aggravated the situation of women who suffer domestic violence? What are the actions of the public system regarding this problem? Thus, we included white literature materials, indexed in the defined databases, published in Portuguese, and responding to the guiding issue, published in the years 2020 and 2021. In the search for the key words "violence", "pandemic" and "women", a total of 4,630 results were found. When applying the selection criteria, 18 studies were chosen. After reading them, 9 were excluded, since they did not deal with violence against women. Thus, the final sample of the literature review consisted of 9 articles. To deepen the research, it was used as a base of information the scientific productions referring to the theme only within the rules of scientific and ethical research approved by the periodicals and research journals, such as: Virtual Health Library (BVS), Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library (Scielo), Electronic Periodicals in Psychology (Pepsic) and Google Scholar. The study ended up showing the existence of few articles and/or research aimed at understanding how the pandemic ended up worsening the data related to domestic violence against women, which can be explained by the fact that it is a recent phenomenon, however, it is also necessary to analyze the lack of discussions around these issues, which points to the invisibilization of violence against women in Brazil. Finally, it is important to emphasize that only after an institutional change that subverts the current division of powers will it be possible to think about any kind of change and reduction of data related to domestic violence against women.